Equity Related Concerns: Impact of Private tutoring in India - Sharma, Harshita (Journal of Education Culture and Society, 2019)
Aim. The paper attempts to explore the impact ofrivate tutoring in light of the equity-related concerns especially in the context of the Indian society. Private tutoring is a phenomenon that has been an intrinsic part of the Indian education system since the 1980s.Methods. The paper is an outcome of the Masters of Philosophy dissertation work of the scholar submitted to National University of Education Planning and Administration, Delhi, India.Results. The structure of private tutoring is such that it mimics the regular school curriculum and modifies itself to match the needs of the school and the children. Any changes in the regular school curriculum bring a change in its supplement as well. It thus behaves like a shadow of the regular schools. Though private tutoring was believed to enhance learning opportunities of weak students, it has now become a 'parity of prestige' issue.Conclusion. The expansion of tutoring has begun to deepen the inequalities already prevalent in the stratified schooling system and society at large.